USE OF MULTISPECTRAL IMAGING IN THE EVALUATION OF BURNINGS AND FOREST FIRES IN KRAHÔLANDIA INDIGENOUS LAND (2003-2014) - Oliveira, Lawrence Nóbrega de; Lazzarini, Gustavo Maximiano Junqueira; Batista, Antonio Carlos; Alves, Kaio Cesar Cardoso de Lima Fonseca; Giongo, Marcos (Floresta, 2015)
Abstract Human actions change the natural occurrences of wildfire. The indigenous communities, during their time of occupation of the Cerrado, probably utilized fire to manipulate the landscape and its resources. In this study, we mapped and analyzed the spatial distribution of burned areas of the Kraholândia Indigenous Land, from 2003 to 2014, using Remote Sensing resources and GIS tools. During the assessed period, the total burned area extended across 1,516,873 ha, representing 4.94 times the sum of Kraholândia Indigenous Land area (306,871 ha). The average annual burned area was 126,406 ha (41.19%), with the year of the largest burned area recorded at 185,297 ha (60.4%) and the year of the smallest burned area was 71,764 ha (23.4%). There were 29,764 ha (9.7%) that had never been burned during the 12 years, and 1,693 ha (0.6%) that had been burned every year of the period. Moreover, the areas that recorded the highest frequency of fire occurrence and burnings were surprisingly not those that produced the largest burned areas over the period. The remote sensing data, allied with methodology employed, succeeded in identifying the frequency of burnings and wildfire in the Krahôlandia Indigenous Land. Resumo Utilização de imagens multispectrais na avaliação das ocorrências de queimadas e incêndios florestais na Terra Indígena Krahôlandia (2003-2014). As ações humanas alteram as ocorrências naturais dos incêndios e queimadas. Os povos indígenas, quando da ocupação do Cerrado, provavelmente usavam o fogo para manipular a paisagem e os seus recursos em várias épocas do ano. Este trabalho teve por objetivo analisar e mapear a distribuição espacial de áreas queimadas na Terra Indígena Krahôlandia, no período de 2003 a 2014, utilizando ferramentas de sensoriamento remoto e SIG. Nos 12 anos avaliados, a área queimada total foi de 1.516.872,51 ha, que representa 4,94 vezes a área total da TI Krahôlandia (306.871,02 ha). A média anual de área queimada foi de 126.406,04 ha (41,19%) com o ano da maior área queimada com 185,297 ha (60,4%) e o ano da área menor com 71,764 ha (23,4%). Houve 29.764 ha (9,7%) que nunca tinham sido queimadas durante os 12 anos, e 1.693 ha (0,6%) que tinham sido queimados todos os doze anos. Além disso, as áreas que registraram a maior frequência de ocorrência de incêndios e queimadas não foram surpreendentemente aquelas que produziram as maiores áreas queimadas ao longo do período. Os dados de sensoriamento remoto aliados com metodologia empregada conseguiu identificar a frequência de ocorrência de queimadas e incêndios florestais na terra indígena Krahôlandia. Palavras-chave: Cerrado; recorrência de fogo.